2019
DOI: 10.1093/jas/skz246
|View full text |Cite
|
Sign up to set email alerts
|

Tannin-containing legumes and forage diversity influence foraging behavior, diet digestibility, and nitrogen excretion by lambs1,2

Abstract: Diverse combinations of forages with different nutrient profiles and plant secondary compounds may improve intake and nutrient utilization by ruminants. We tested the influence of diverse dietary combinations of tannin- (sainfoin-Onobrichis viciifolia; birdsfoot trefoil-Lotus corniculatus) and non-tannin- (alfalfa-Medicago sativa L.) containing legumes on intake and diet digestibility in lambs. Freshly cut birdsfoot trefoil, alfalfa, and sainfoin were offered in ad libitum amounts to 42 lambs in individual pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Alternatively, CT may still be active under the pH level (5.0) of the proximal small intestine and interfere with endogenous and microbial proteolytic enzymes, increasing the proportion of protein in the feces [94]. In support of this, Lagrange et al [74] observed that beef cattle grazing sainfoin partitioned more N to feces (30.1% vs. 22.7%, respectively) than animals grazing birdsfoot trefoil, and sheep fed fresh sainfoin showed greater fecal N than sheep fed pure birdsfoot trefoil or alfalfa (31.5% vs. 26.6%, respectively; [113]). This may reduce N retention, as observed for sainfoin diets [114].…”
Section: Condensed Tannin-protein Complexes and Reductions In Urinary N Excretionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Alternatively, CT may still be active under the pH level (5.0) of the proximal small intestine and interfere with endogenous and microbial proteolytic enzymes, increasing the proportion of protein in the feces [94]. In support of this, Lagrange et al [74] observed that beef cattle grazing sainfoin partitioned more N to feces (30.1% vs. 22.7%, respectively) than animals grazing birdsfoot trefoil, and sheep fed fresh sainfoin showed greater fecal N than sheep fed pure birdsfoot trefoil or alfalfa (31.5% vs. 26.6%, respectively; [113]). This may reduce N retention, as observed for sainfoin diets [114].…”
Section: Condensed Tannin-protein Complexes and Reductions In Urinary N Excretionsmentioning
confidence: 96%
“…In support of this, Lagrange et al [74] observed a 33% greater dry matter intake (DMI) and 30 to 50% greater ADG in heifers that grazed a 3-way choice among alfalfa, sainfoin, and birdsfoot trefoil relative to the average DMI and ADG from animals grazing the same three species in monocultures, suggesting a synergism among pasture species when these were consumed together. Similarly, sheep that were offered a choice of different legumes and selected 50% alfalfa, 35% sainfoin, and 15% birdsfoot trefoil had 10% greater DMI and DM digestibility than for the average DMI value calculated from the same proportions of these forages when they were fed separately [113]. On the other hand, Wang et al [147] observed similar feed intakes in beef steers grazing pure alfalfa or mixed alfalfa-sainfoin pastures containing up to 35% sainfoin; Christensen [170], when feeding a mixture of alfalfa-birdsfoot trefoil hays to dairy cows, did not find differences in DMI relative to feeding pure alfalfa.…”
Section: Forage Diversity In Beef Cattle Production Systemsmentioning
confidence: 99%
“…Further, animals can be raised in intercropping systems to graze on crop residue, contributing to soil fertility and pest management. By incorporating a variety of forage species (e.g., alfalfa, sainfoin, birdsfoot trefoil, ryegrass, and clover) into pastures, a more diverse and nutritious diet can be provided to animals and can promote biodiversity in the ecosystem, as well as helping to make the pastures more climate-resilient [130][131][132]. Integrating multiple livestock species into crop production or agroforestry systems, such as using chickens to control pests in orchards or goats, sheep, and cows to fertilize fields, may increase system effectiveness and decrease the requirement for synthetic inputs [108].…”
Section: The Principles Of Preserving Biodiversity Synergy and Soil H...mentioning
confidence: 99%
“…This diversity allows for individuals to select a range of plant components that differ in their harvestability and nutritive value and allows for variation in preferences to be expressed. Having a forage resource that is diverse can increase feed intake (Lagrange and Villalba 2019) and has been attributed to improved animal welfare (Beck and Gregorini 2020). In a monoculture system such as a brassica crop, there is a limited ability to select a diverse diet and therefore this could potentially have detrimental impacts on some individuals.…”
Section: Introductionmentioning
confidence: 99%